Clinical characteristics of patients with intraocular lens calcification after pars plana vitrectomy - Bopp, Silvia; Özdemir, Hüseyin Baran; Aktaş, Zeynep; Khoramnia, Ramin; Yildirim, Timur Mert; Schickhardt, Sonja; Auffarth, Gerd U.; Özdek, Şengül (Diagnostics, 2023)
Aim: To determine the clinical risk factors that may increase the occurrence of intraocular lens (IOL) calcification in patients who had undergone pars plana vitrectomy (PPV). Methods: The medical records of 14 patients who underwent IOL explantation due to clinically significant IOL opacification after PPV were reviewed. The date of primary cataract surgery, technique and implanted IOL characteristics; the time, cause and technique of PPV; tamponade used; additional surgeries; the time of IOL calcification and explantation; and IOL explantation technique were investigated. Results: PPV had been performed as a combined procedure with cataract surgery in eight eyes and solely in six pseudophakic eyes. The IOL material was hydrophilic in six eyes, hydrophilic with a hydrophobic surface in seven eyes and undetermined in one eye. The endotamponades used during primary PPV were C2F6 in eight eyes, C3F8 in one eye, air in two eyes and silicone oil in three eyes. Two of three eyes underwent subsequent silicone oil removal and gas tamponade exchange. Gas in the anterior chamber was detected in six eyes after PPV or silicone oil removal. The mean interval between PPV and IOL opacification was 20.5 ± 18.6 months. The mean BCVA in logMAR was 0.43 ± 0.42 after PPV, which significantly decreased to 0.67 ± 0.68 before IOL explantation for IOL opacification (p = 0.007) and increased to 0.48 ± 0.59 after the IOL exchange (p = 0.015). Conclusions: PPV with endotamponades in pseudophakic eyes, particularly gas, seems to increase the risk for secondary IOL calcification, especially in hydrophilic IOLs. IOL exchange seems to solve this problem when clinically significant vision loss occurs.
Veröffentlicht: 1. Juni 2023
Gesehen am 24.07.2023